A combinatorial DNA assembly approach to biosynthesis of N-linked glycans in E. coli. (13th January 2023) - Passmore, Ian J; Faulds-Pain, Alexandra; Abouelhadid, Sherif; Harrison, Mark A; Hall, Catherine L; Hitchen, Paul; Dell, Anne; Heap, John T; Wren, Brendan W
Abstract: Glycoengineering of recombinant glycans and glycoconjugates is a rapidly evolving field. However, the production and exploitation of glycans has lagged behind that of proteins and nucleic acids. Biosynthetic glycoconjugate production requires the coordinated cooperation of three key components within a bacterial cell: a substrate protein, a coupling oligosaccharyltransferase, and a glycan biosynthesis locus. While the acceptor protein and oligosaccharyltransferase are the products of single genes, the glycan is a product of a multigene metabolic pathway. Typically, the glycan biosynthesis locus is cloned and transferred en bloc from the native organism to a suitable Escherichia coli strain. However, gene expression within these pathways has been optimized by natural selection in the native host and is unlikely to be optimal for heterologous production in an unrelated organism. In recent years, synthetic biology has addressed the challenges in heterologous expression of multigene systems by deconstructing these pathways and rebuilding them from the bottom up. The use of DNA assembly methods allows the convenient assembly of such pathways by combining defined parts with the requisite coding sequences in a single step. In this study, we apply combinatorial assembly to the heterologous biosynthesis of the Campylobacter jejuni N -glycosylation ( pgl ) pathway in E. coli. We engineered reconstructed biosynthesis clusters that faithfully reproduced the C. jejuni heptasaccharide glycan. Furthermore, following a single round of combinatorial assembly and screening, we identified pathway clones that outperform glycan and glycoconjugate production of the native unmodified pgl cluster. This platform offers a flexible method for optimal engineering of glycan structures in E. coli .